On a new species of the spider genus Attacobius Mello-Leitão (Araneae: Corinnidae) from Brazilian Cerrado - Bonaldo, Alexandre B.; Pesquero, Marcos A.; Brescovit, Antonio D. (Zootaxa, 2018)
At the time the genus Attacobius Mello-Leitão, 1925 was first acknowledged as a member of the subfamily Corinninae, Corinnidae, by Platnick & Baptista (1995), only three species were recognized. Since then, that number has increased to 15 currently valid species (Bonaldo & Brescovit 1998; 2005; Pereira-Filho et al. 2018). Recently we had the opportunity to discover an additional species of Attacobius, collected in association with fire ants of the genus Solenopsis Westwood in the State of Goiás, Midwest Brazil, a region that harbors a large portion of the Brazilian Cerrado, one of the most threatened savannas in the planet. Attacobius lavape n. sp., described below, appears to belong to the same group of species as A. verhaaghi Bonaldo & Brescovit, 1998 and A. lamellatus Bonaldo & Brescovit, 2005, since these three species share, in the male palp, the presence of an unsclerotized median lobe on the retrolateral tibial apophysis (Figs 9, 11).